CSR disclosure and debt financing in Indonesia - Aiman, Aiman; Rifandy, Tastaftiyan (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2024)
This research examines the relationship between CSR and company financing as seen from short-term debt financing and long-term financing. The data used is non-oil and gas manufacturing companies listed on the Indonesia Stock Exchange in the 2018-2022 period. There were 350 observations made from a total sample of 70 companies. Judging from the existing phenomenon, there are still many manufacturing companies that are still limited in accessing easy and cheap financing, especially in Indonesia. The results of the research show that CSR disclosure has no effect on financing.